Maternal predation risk increases offspring's exploration but does not affect schooling behavior. (21st July 2020) - Cattelan, Silvia; Herbert-Read, James; Panizzon, Paolo; Devigili, Alessandro; Griggio, Matteo; Pilastro, Andrea; Morosinotto, Chiara
Abstract: The environment that parents experience can influence their reproductive output and their offspring's fitness via parental effects. Perceived predation risk can affect both parent and offspring phenotype, but it remains unclear to what extent offspring behavioral traits are affected when the mother is exposed to predation risk. This is particularly unclear in live-bearing species where maternal effects could occur during embryogenesis. Here, using a half-sib design to control for paternal effects, we experimentally exposed females of a live-bearing fish, the guppy ( Poecilia reticulata ), to visual predator cues and conspecific alarm cues during their gestation. Females exposed to predation risk cues increased their antipredator behaviors throughout the entire treatment. Offspring of mothers exposed to the predation stimuli exhibited more pronounced exploratory behavior, but did not show any significant differences in their schooling behavior, compared to controls. Thus, while maternally perceived risk affected offspring's exploration during early stages of life, offspring's schooling behavior could be influenced more by direct environmental experience rather than via maternal cues. Our results suggest a rather limited role in predator-induced maternal effects on the behavior of juvenile guppies. Abstract : Offspring of mothers exposed to prolonged predation risk had consistently more pronounced exploratory behavior, but did not show any significant differences in schooling, than offspring of unexposed mothers. Thus, as a consequence of the predation risk experienced by their mothers, offspring explore more, which may increase their propensity to disperse away from risky areas.